Oral and dermal diflubenzuron exposure causes a hypothalamic–pituitary–thyroid (HPT) axis disturbance in the Mongolian racerunner (Eremias argus). (January 2018) - Chang, Jing; Wang, Huili; Xu, Peng; Guo, Baoyuan; Li, Jianzhong; Wang, Yinghuan; Li, Wei
Abstract: Diflubenzuron (DFB) is a potential endocrine-disrupting chemical. However, its thyroid endocrine effect on reptiles has not been reported. In this study, immature lizards ( Eremias argus ) were exposed to 20 mg kg −1 DFB once a week for 42 days through oral or dermal routes. Their body weight, plasma thyroid hormone levels, thyroid gland histology and the transcription of hypothalamic–pituitary–thyroid (HPT) axis-related genes in different tissues were assessed to explore the effects of DFB on the HPT axis of lizards. The body weight decreased significantly only after the dermal exposure to DFB. Triiodothyronine (T3) to thyroxine (T4) ratio in the male plasma also significantly increased after the dermal exposure. After oral exposure, the activity of thyroid gland was positively related to the thyroid hormone levels. Furthermore, the alterations in thyroid hormone levels affected the HPT axis-related gene expression, which was tissue dependent and sexually selected. The thyroid hormone receptor genes (tr α and trβ ) in the brain and thyroid were more sensitive to oral exposure. However, only the dermal treatment affected the trα, trβ and type 2 deiodinase ( dio2 ) genes in the male liver. These results suggest that DFB exposure caused sex-specific changes in the thyroid function of lizards, and the dermal treatment may be an important route for the risk assessment of reptiles. Graphical abstract: Highlights: Only dermal exposure caused significant decrease in lizard body weight. T3/T4 ratio in the male lizard significantly increased after dermal exposure. trα and trβ genes in the brain and thyroid were more sensitive to oral exposure. Only the dermal treatment affected the trα, trβ and dio2 genes in the male liver. Abstract : The oral and dermal exposure to diflubenzuron caused different toxic effects on the HPT axis of lizards.